The Effect of The Tiktok Application on Students' Mathematical Reasoning - Anisa Khoiriyah; Choirudin Choirudin; Eka Fitria Ningsih (Delta-Phi: Jurnal Pendidikan Matematika, 2023)
The increasing number of users networking social media TikTok among senior high school students in Indonesia, of course, will influence learning students, especially in terms of digital skills in mathematics. Counting is essential because students can count like that appearance so that they will later encounter a perceived problem that is difficult in learning mathematics. This research aims to determine how much influence TikTok social media users have against reasoning mathematics in students. This research adopts the quantitative experimental group control method before and after the experiment was designed, and the sample in this study adopted the cluster random sampling method. Instruments used from the paper The test consists of 5 pre-tests and five post-tests in class X TB A SMKN 3 Metro. Data analysis uses the Paired Samples Statistics Test. The results of the research using paired samples statistics conclude that the application of TikTok is influential and significant to reasoning mathematics in students; the average pre-test score is 45.88, and the average score post-test is 87.06. As such, it has been proven that TikTok influences reasoning mathematics in students.